Phenetic relationship between Lepisorus (J. SM.) Ching (Pteridophyta: Polypodiaceae) and its related genera - Chatan, Wannachai; Boonkerd, Thaweesakdi; Baum, Bernard R. (Bangladesh Journal of Plant Taxonomy, 2009)
Multivariate analyses based on morphological and anatomical characters have been performed to investigate the phenetic relationship and to clarify the circumscriptions of the genus Lepisorus (J.Sm.) Ching and its related genera, namely Neocheiropteris Christ, Paragramma T. Moore and Platygyria Ching & S.K. Wu. The dendrogram of cluster analysis separated the plants into three groups at Gower similarity coefficient 0.75. Group 1 and Group 2 consisted of Neocheiropteris palmatopedata (Baker) H. Christ and four species of Platygyria, respectively. Group 3 was Neocheiropteris ensata Ching and two species of Paragramma deeply embedded in the Lepisorus s.s. Canonical discriminant analysis supported the classification inferred from the clustering results. Based on these results, Platygyria and N. palmatopedata should be recognized as distinct genera. On the other hand, N. ensata and the genus Paragramma should be merged to the genus Lepisorus. Keywords: Lepisorus; Paragramma; Platygyria; Cluster analysis; Canonical discriminant analysis. DOI: 10.3329/bjpt.v16i2.3924 Bangladesh J. Plant Taxon. 16(2): 99-113, 2009 (December)